Accelerating India's development: a state-led roadmap for effective governance - Muralidharan, Karthik (Gurugram Penguin Random House India, 2024)
Accelerating India's Development: A State-Led Roadmap for Effective Governance
Keywords: Economy Sector; Economic- Production; Economic Development and Growth